CANCEL CULTURE KASUS KEKERASAN SEKSUAL DI KALANGAN FOLLOWERS AUTOBASE TWITTER @AREAJULID - Yayang Eka Januarda Nisa; Yuhastina; Nurhadi (Institut Pendidikan Indonesia, 2022)
Social media is currently experiencing very rapid development. So it can provide a virtual open space, as is the case with Twitter social media, which offers a forum for netizens to gather and discuss certain topics. The problem with netizens in expressing their own opinions often ends in punishing someone who is deemed to have made a mistake, which is often called cancel culture and experts have different opinions regarding cancel culture. The cancel culture phenomenon has become a relatively growing discussion and problem on social media and is considered a post-modern sociological problem. This research aims to try to provide an overview in the field regarding the cancel culture phenomenon in cases of sexual violence as part of a tool of social control. This research uses a qualitative phenomenological method, data is taken from interviews and observations with 7 followers of the @areajulid autobase account. The results of the research concluded that 1) The sources criticized perpetrators of sexual violence in different ways. 2) Cancel culture is a tool of social control through ridicule and ridicule as well as rumors/gossip. So, through social control of cancel culture on Twitter social media as an effort to minimize cases of social pathology or social crimes, through implementing cancel culture as a preventive effort in using social media wisely.